The importance of using polyethylene bags in preserving apricots (Royal) and peaches (Al-Ghatmi) during refrigerated storage. (Latakia University Journal -Biological Sciences Series, 2023)
The study was conducted on the fruits of apricot (Royal) and peach (AlGhatmi). With the aim of knowing the effect of polyethylene bags on maintaining the most important quality characteristics and safety of fruits during refrigerated storage, At a temperature of (3)°C and a relative humidity of (90-95)%, And compare the results with the control fruits stored under the same storage conditions. Some quality indicators were measured (Total acidity TA%, Total Soluble Solids TSS%) (once a week) until the end of the storage period, which lasted (30) days for the (Royal), and (60) days for the (Al-Ghatmi).   The results showed that there is a significant effect of the modified gaseous atmosphere on the studied indicators For all fruits stored in polyethylene bags compared to control fruits, The highest percentage of TA was (1.6-0.72)% in apricot and peach fruits Stored in bags respectively, While the percentage of TA was (0.75-0.2)% for the control fruits in apricot and peach, respectively. The percentage of (TSS) increased for all the fruits stored as a control and to a lesser extent in the fruits stored in polyethylene bags. The highest percentage was (21.4)% for the control fruits in apricot and (18.2)% for the control fruits for peach, While the percentage of TSS was (18.9-16.6)% in apricot and peach fruits stored under modified gaseous atmosphere, respectively.